2018
DOI: 10.1159/000488271
|View full text |Cite
|
Sign up to set email alerts
|

Glycyrrhizin Treatment Facilitates Extinction of Conditioned Fear Responses After a Single Prolonged Stress Exposure in Rats

Abstract: Background/Aims: Impaired fear memory extinction is widely considered a key mechanism of post-traumatic stress disorder (PTSD). Recent studies have suggested that neuroinflammation after a single prolonged stress (SPS) exposure may play a critical role in the impaired fear memory extinction. Studies have shown that high mobility group box chromosomal protein 1 (HMGB-1) is critically involved in neuroinflammation. However, the role of HMGB-1 underlying the development of impairment of fear memory extinction is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 58 publications
2
25
0
Order By: Relevance
“…PTSD can be classified into four symptoms: intrusive thoughts, avoiding reminders, negative thoughts and feelings, and arousal and reactive symptoms; the severity of these symptoms may vary ( Alaqeel et al, 2019 ; Lai et al, 2018 ; Panagioti et al, 2015 ; Piotrowski & Range, 2019 ). Intrusive thoughts refer to the intrusion of painful memories or emotions to the consciousness, resulting in feeling or acting as if the patient is experiencing the actual trauma, and are marked by physiological responses such as severe mental pain and sudden increases in heartbeat ( Piotrowski & Range, 2019 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…PTSD can be classified into four symptoms: intrusive thoughts, avoiding reminders, negative thoughts and feelings, and arousal and reactive symptoms; the severity of these symptoms may vary ( Alaqeel et al, 2019 ; Lai et al, 2018 ; Panagioti et al, 2015 ; Piotrowski & Range, 2019 ). Intrusive thoughts refer to the intrusion of painful memories or emotions to the consciousness, resulting in feeling or acting as if the patient is experiencing the actual trauma, and are marked by physiological responses such as severe mental pain and sudden increases in heartbeat ( Piotrowski & Range, 2019 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…15 Our previously published results found that administration of glycyrrhizin in the basolateral amygdala prevented the development of a single long-term stress-induced fear-regression disorder, suggesting that glycyrrhizin has an antagonistic effect on PTSD. 16 However, its specific molecular mechanism requires further research, which is the starting point of the present study.…”
Section: Glycyrrhizinmentioning
confidence: 99%
“…Alternatively, the oxidized state of HMGB-1, designated by the formation of disulfide linkages, is capable of potentiating proinflammatory signaling as discussed above but lacks chemotactic abilities (Yang et al, 2012 ). Although the majority of studies assessing the involvement of HMGB-1 in microglial priming have come from studies using inescapable foot shock (Yang et al, 2012 ; Weber et al, 2015 ), chronic unpredictable stress (Franklin et al, 2018 ), and single prolonged stress (Lai et al, 2018 ), exposure to social stressors such as social defeat is known to enhance the intracellular concentration of reactive oxygen species (ROS; see section Oxidative Stress/Reactive Oxygen Species). Therefore, it is highly plausible that HMGB-1 may also contribute to the emergence of social stress-induced behavioral deficits.…”
Section: Sources Of Stress-induced Neuroinflammationmentioning
confidence: 99%